Financial Ratio Analysis of PT Bank Negara Indonesia (Persero) Tbk Year 2018-2022 - Sabilah, Dinda; Ariyani, Rini; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The aim of this research is to determine the liquidity, solvency and profitability ratios at PT Bank Negara Indonesia (Persero) Tbk for the 2018-2022 period. This research uses quantitative methods with a descriptive approach. The results of the discussion in this research are that with liquidity ratios consisting of Quick Ratio, Banking Ratio, Loan to Assets Ratio, and Loan to Deposit Ratio, it can be seen that financial conditions change each period, namely the amount of loans given is less than the amount of money saved by customers. Based on an analysis of the solvency ratio at PT Bank Negara Indonesia (Persero) Tbk for the 2018-2022 period, it shows that the primary ratio and capital adequacy ratio tend to increase, making it easier for the bank to manage losses that occur in each period. PT Bank Negara Indonesia (Persero) Tbk's profitability ratio tends to vary due to declines and increases. However, in the 2020 period the level of health tends to be poor based on the ROA and ROE values ??because it has not been able to generate profits from the capital it has. It can be concluded that from all the liquidity, solvency and profitability ratio analyzes that have been carried out, it can be seen that the financial performance of PT Bank Negara Indonesia (Persero) Tbk for the 2018-2022 period has increased quite significantly.